Indole-2-carboxamide derivatives: a patent evaluation of WO2015036412A1 - Zitko, Jan; Dolezal, Martin (Expert opinion on therapeutic patents, 2015)
INTRODUCTION: Hippocampal neurogenesis in adults is a new and attractive target for the treatment and prevention of neurodegenerative and neuro-psychiatric diseases. Recently, neurogenesis stimulating activity was observed in some of the commonly used small molecule drugs such as antidepressants and atypical antipsychotics. Stimulation of neurogenesis is attractive mainly due to its wide scope of application, ranging from depressions, schizophrenia, dementia, Parkinson`s and Alzheimer`s Disease to various brain injuries. AREAS COVERED: New compounds based on 7-phenyl or 7-pyridinyl-1H-indole-2-carboxamide showed interesting neural stem cell proliferation inducing activity in vitro and were claimed as potential therapeutics for various neurodegenerative and neuropsychiatric diseases as well as brain injuries. The potential of the presented compounds is evaluated with respect to other small molecule neurogenesis inducers in literature. EXPERT OPINION: Nanomolar in vitro activities of presented compounds and their favorable physico-chemical properties, giving a fair chance of good oral bioavailability and sufficient CNS penetration, make these compounds promising drug candidates. The biggest drawback of the presented application is the absence of pharmacokinetics, toxicity and in vivo activity data. On the other hand, the high number of applications in this area (seven published in last two years) indicates that Hoffmann-La Roche takes it seriously.
Keywords: dospělí; patenty jako téma; Animals; Indoles; Neurogenesis; proliferace buněk; Neurodegenerative Diseases; Brain Injuries; hipokampus; indoly; Adult; Biological Availability; duševní poruchy; neurogeneze; biologická dostupnost; lidé; Neural Stem Cells; poranění mozku; neurodegenerativní nemoci; nervové kmenové buňky; Drug Delivery Systems; Cell Proliferation; Hippocampus; Patents as Topic; Mental Disorders; lékové transportní systémy; zvířata; Humans